Association between stress hyperglycemia ratio and acute kidney injury development in patients with sepsis: a retrospective study - Fang, Yipeng; Dou, Aizhen; Zhang, Ying; Xie, Hui; Zhang, Yunfei; Cui, Yan; Xie, Keliang (Frontiers in Endocrinology, 2025)
BackgroundStress hyperglycemia ratio (SHR), which adjusts blood glucose levels using glycated hemoglobin to eliminate the influence of chronic hyperglycemia, has been demonstrated to have superior predictive value than absolute hyperglycemia. However, its predictive value for sepsis-associated acute kidney injury (SA-AKI) remains unclear. This study aimed to investigate the relationship between the SHR and the risk of developing SA-AKI.MethodsData were extracted from the Medical Information Mart for Intensive Care IV (MIMIC-IV) database. Restricted cubic splines (RCS) were employed to depict the relationship between SHR and the likelihood of SA-AKI, determining an optimal cut-off value. Based on this threshold, patients were categorized into two groups. Logistic regression was utilized to evaluate SHR’s predictive value for SA-AKI, with adjustments for confounding variables. Propensity score matching (PSM) was applied to balance baseline characteristics. Subgroup and sensitivity analyses were conducted.ResultsA total of 2,249 patients were included. The RCS curve indicated a non-linear positive association between SHR and the likelihood of SA-AKI (P for non-linearity < 0.001), with an optimal cut-off at 1.55. Accordingly, patients were divided into SHR ≤ 1.55 and SHR > 1.55 subgroups, comprising 1,131 and 1,118 individuals, respectively. A higher incidence of SA-AKI was observed in the SHR > 1.55 group (38.64% vs. 27.23%, P < 0.001). This association persisted after baseline adjustment through PSM. Logistic regression analysis confirmed that SHR > 1.55 was linked to increased odds of SA-AKI in both unadjusted (OR: 1.68, P < 0.001) and adjusted models (OR: 1.73, P < 0.001), with SHR ≤ 1.55 serving as the reference. In subgroup analysis, all subgroups consistently demonstrated a significant association between SHR > 1.55 and elevated odds of SA-AKI (all OR > 1). Sensitivity analysis validated that SHR > 1.55 remained significantly correlated with SA-AKI occurrence in the survival subgroup (OR: 1.46, P < 0.001) and the non-CKD subgroup (OR: 1.69, P < 0.001).ConclusionThe findings indicate a non-linear positive relationship between SHR and the likelihood of SA-AKI in patients with sepsis, suggesting that SHR could be a potential predictor for SA-AKI.